Internal Control Of Village Apparatus On Preventing Village Financial Mismanagement: The Moderating Role Of Organizational Culture - Rino Rafael; Bernard Realino (PT PUSTAKA CENDEKIA GROUP, 2024)
This study aims to analyze the effect of internal control on preventing village financial mismanagement, the effect of organizational culture on preventing village financial mismanagement, and the role of organizational culture as a moderating variable in strengthening the influence of internal control on efforts to prevent village financial mismanagement. This research uses a quantitative approach with an explanatory research design. This study involved one hundred fifty village heads in Wonogiri Regency, who were selected because they have a strategic role in the process of managing, controlling, and supervising village financial governance. Data were collected through a survey method using a structured questionnaire measured with a Likert scale. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) after all research instruments were tested and confirmed to be valid and reliable. The results show that organizational culture has a positive and significant effect on preventing village financial mismanagement. Internal control also has a positive and significant effect on preventing village financial mismanagement, and it represents the variable with the strongest direct influence in the research model. Furthermore, organizational culture is proven to moderate the relationship between internal control and preventing village financial mismanagement positively and significantly. These findings indicate that the prevention of village financial mismanagement does not rely solely on the effectiveness of internal control systems but also requires a strong organizational culture to support the consistent and sustainable implementation of control mechanisms. Therefore, strengthening internal control accompanied by the development of a healthy organizational culture becomes an important strategy in improving village financial governance and ensuring greater transparency and accountability in village financial management.